Pengaruh rasio profitabilitas, rasio leverage, dan rasio likuiditas terhadap harga saham - Fahrizal, Rifky; Hendayana, Yana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The aim of this research is to determine the effect of profitability, leverage and liquidity ratios on stock prices of metal & mineral sub-sector companies listed on the IDX for the 2018-2021 period. Obtained as many as 7 (seven) samples of companies using purposive sampling method. This research uses the associative method with multiple linear regression data analysis techniques and hypothesis testing assisted by the SPSS 26 program, which includes a partial test (t test) and simultaneous test (F test) to determine the effect between variables. The results of the research state that profitability does not have a partial effect on stock prices with a significant profitability of 0.628, leverage does not have a partial effect on stock prices with a significant leverage of 0.533, liquidity has a partial effect on stock prices with a significant 0.008. The results of the research state that profitability, leverage, and liquidity simultaneously affect stock prices with a significant 0.014. This research is expected to help companies to improve financial performance in order to avoid a decline, can help investors in making investment decisions.